2016
DOI: 10.5296/ije.v8i2.9148
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Algebra Underlying High School Student´s Self-Efficacy Judgment to Solve Mathematical Problems in the Classroom or Online

Abstract: <p>This study includes a sample of 112 high school students who provided self-efficacy<br />judgments to solve math problems. Thirty-six experimental conditions called scenarios were<br />created for this study by combining 4 factors regarding solving mathematical problems<br />(modality, degree of difficulty, structuring, and relevance of the task). Each scenario<br />described a hypothetical context that required the participant to imagine an activity to<br />reinforce the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Here, it is relevant to mention that the appointed clusters relate more to the perceived self-efficacy than to the identified factor information integration cognitive rule. This is interesting because previous research carried on middle level education environments (Briones et al, 2016) found that even when students considered in this research used the same information integration rule (summative), factor valuation in both groups was significantly different. The reason of why factor information integration and factor weight valuation is different between middle students and high level education students is not clear.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Here, it is relevant to mention that the appointed clusters relate more to the perceived self-efficacy than to the identified factor information integration cognitive rule. This is interesting because previous research carried on middle level education environments (Briones et al, 2016) found that even when students considered in this research used the same information integration rule (summative), factor valuation in both groups was significantly different. The reason of why factor information integration and factor weight valuation is different between middle students and high level education students is not clear.…”
Section: Discussionmentioning
confidence: 67%
“…The experimental design used in this study consisted of orthogonal combination of factor levels regarding assigned types of task to learn mathematics and the education modality used to deliver these tasks (Briones-Rodriguez et al, 2016). That is, a 2(modality: virtual vs. face to face instruction) x 2(task difficulty: high vs. low) x 3 (level of teaching structure: High vs. medium vs. low) x 3 (task relevance: High vs. medium vs. low).…”
Section: Methodology Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Mexican students have been shown to adopt a systematic thinking process, whereby they rely on summative rules to make academic self-efficacy judgments (e.g., Briones-Rodriguez et al, 2016;Villarreal-Trevino et al, 2017), and make cheating desire judgments (Morales-Martinez et al, 2019).…”
Section: Present Studymentioning
confidence: 99%